Encyclopedia of Feeding and Eating Disorders - Wade, Tracey (Springer Singapore : Imprint: Springer, 2017)
The field of feeding and eating disorders represents one of the most challenging areas in mental health, covering childhood, adolescent and adult manifestations of the disorders and requiring expertise in both the physical and psychological issues that can cause, maintain, and exacerbate these disorders. The scope of the book is an overview of all the feeding and eating disorders from "bench to bedside", incorporating recent changes introduced into the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5). The aim is to present one of the first complete overviews of the newly defined area of feeding and eating disorders with respect to genetics, biology and neuroscience through to theory and its application in developing clinical approaches to the prevention and treatment of feeding and eating disorders.
Keywords: Medicine.; Health care management.; Health services administration.; Health psychology.; elektronické knihy; electronic books